OBME For Learning Model Development Basic Students Locomotor Movement - bayu thomi Rizal; Arodotonafo Wiratama Hulu (JIPES - JOURNAL OF INDONESIAN PHYSICAL EDUCATION AND SPORT, 2021)
The purpose of this study was to produce a learning model for Outbound Basic Motion Education (OBME) for basic locomotor movements of elementary school children. The study was conducted to obtain information about the application of the Outbound Basic Motion Education (OBME) learning model. This study uses the Research & Development (R&D) development research method from Borg and Gall. Small group test of 20 students at Negeri 24 Kramat Jati Elementary School, East Jakarta with 45 model items. In a large group trial of 60 students with 31 item models. The effectiveness test of 30 students used the locomotor test with the one group pretest-posttest design, the pre-test data was obtained for 42.7333 and the post-test 72.6333 so that there is a difference with a difference of 29.9, meaning that there is a significant difference and the value of the effectiveness test The post-test is higher than the pre-test score, so based on this it can be concluded that the application of the Outbound Basic Motion Education (OBME) learning model developed by this writer is effective in improving basic locomotor movement skills of elementary school children. Based on the results obtained, it can be concluded that: (1) With this Outbound Basic Motion Education (OBME) learning model students can learn more effectively and efficiently, (2) with this Outbound Basic Motion Education (OBME) learning model, an increase is obtained. It is shown in the pre-test and post-test results that there is a significant difference.